Assessment of selected natural wetlands for treating wastewater contaminants from adjacent human activities - Monapathi, Mzimkhulu; Meno, Ntefeleng; Klink, Michael; Okoli, Bamidele; Johannes, (Edelweiss Applied Science and Technology, 2026)
Wetlands function as natural wastewater treatment systems but are increasingly degraded by human activities and climate change. This study evaluated the capacity of selected natural wetlands to reduce wastewater contaminants from adjacent human activities. Water samples were collected at predetermined input and output points during dry and wet seasons and analyzed for physicochemical parameters, heavy metals, and microbiological indicators. pH ranged from 6.66 to 7.6, and the temperature from 24 to 27.3 °C. Turbidity decreased markedly from 84 to 9 NTU in the dry season and from 42 to 8 NTU in the wet season. Heavy metals also declined between the input and the output, including copper (0.81-0.72 mg/L in the dry season; 0.46-0.27 mg/L in the wet season), lead (1.16-0.84 mg/L; 1.01-0.89 mg/L), silver (0.50-0.30 mg/L; 0.59-0.25 mg/L), and zinc (0.50-0.24 mg/L; 0.48-0.28 mg/L). Nutrients and microbial indicators showed similar reductions. Approximately 80% of the measured parameters were higher at the wetland input than at the output. These wetlands, located upstream of the Vaal River, significantly reduce pollutant loads, highlighting their importance for water quality protection and the urgent need for conservation.